Pengaruh Perceived Service Quality dan Switching Cost terhadap Customer Loyalty - Hidayaturrakhma, Dhia Annisa; Tarmedi, Eded; Lisnawati, Lisnawati (Business Education Program of Universitas Pendidikan Indonesia, 2019)
Abstract: This research aims to determine the Effect of Perceived Service Quality and Switching Cost on Customer Loyaly in the IM3 Ooredoo Users in Indonesia. This research is a descriptive verification research, using explanatory survey method by simple random sampling technique with 150 respondents and the data were analized by multiple regression analysis with the help of SPSS 24.0. The outcome of this study indicate that the concept of perceived service quality is fairly high category, the concept of switching cost is fairly high category, the concept of customer loyalty is fairly high category, and the customer loyalty is influenced by both perceived service quality and switching cost.Keywords: Perceived Service Quality; Switching Cost; Customer LoyaltyÂ